2014
DOI: 10.1002/2014jf003156
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the significance of abrasion and selective transport for downstream fluvial grain size evolution

Abstract: It is well known that pebble diameter systematically decreases downstream in rivers. The contribution of abrasion is uncertain, in part because (1) diameter is insufficient to characterize pebble mass loss due to abrasion and (2) abrasion rates measured in laboratory experiments cannot be easily extrapolated to the field. A recent geometric theory describes abrasion as a curvature-dependent process that produces a two-phase evolution: in Phase I, initially blocky pebbles round to smooth, convex shapes with lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
104
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 67 publications
3
104
0
1
Order By: Relevance
“…Examination of gravel-sand transitions along downstream river profiles indicates that the mode of bed-material transport may switch abruptly from near-threshold (gravel-bedded) to suspension (sand-bedded) (Miller et al (2014); Venditti et al (2015); Venditti et al (2010);Singer (2010);Singer (2008)), and hydraulic considerations 15 have suggested that susceptibility to suspension increases rapidly as grain size decreases across the gravel to sand range (Lamb and Venditti (2016)). On the other hand, recent compilations of global data sets have been used to suggest that rivers exhibit a continuum of transport states -from near threshold through to full suspension -and that bankfull Shields stress varies smoothly with grain size, slope and particle Reynolds number (Parker et al (2007); Wilkerson and Parker (2010); Li et al (2015); Trampush et al (2014)).…”
mentioning
confidence: 99%
“…Examination of gravel-sand transitions along downstream river profiles indicates that the mode of bed-material transport may switch abruptly from near-threshold (gravel-bedded) to suspension (sand-bedded) (Miller et al (2014); Venditti et al (2015); Venditti et al (2010);Singer (2010);Singer (2008)), and hydraulic considerations 15 have suggested that susceptibility to suspension increases rapidly as grain size decreases across the gravel to sand range (Lamb and Venditti (2016)). On the other hand, recent compilations of global data sets have been used to suggest that rivers exhibit a continuum of transport states -from near threshold through to full suspension -and that bankfull Shields stress varies smoothly with grain size, slope and particle Reynolds number (Parker et al (2007); Wilkerson and Parker (2010); Li et al (2015); Trampush et al (2014)).…”
mentioning
confidence: 99%
“…A fent említett méreti és alaki sajátosságok, továbbá a folyó szakasza mentén való több mint 400 km-es távolság a forrás -régiótól kizárják a tömbök klasszikus folyóvízi szál lí tó -dásának lehetőségét, hiszen ilyen távú görgetve szállí tás esetén az ilyen nagyméretű hömpölyök mozgatá sához szük séges óriási vízsebesség mellett a vizsgált hor dalék meg mun kált -sága, koptatottsága nagy fokú lenne (pl. KRUMBEIN 1941, LINDSEY et al 2007, ATTAL & LAVÉ 2009, MILLER et al 2014.…”
Section: Diszkusszióunclassified
“…Further, implicit in this practice (and by extension in sediment mixing models) is an untested assumption that pebbles with different abrasion rates are not able to statistically change (i.e., distort) the detrital age distribution of sands. However, fluvial abrasion of clasts has long been considered as one of the main drivers of mineral liberation from coarser‐ to finer‐size fractions and thus one of the processes that, along with selective transport, promote downstream fining along a river (Attal & Lavé, , ; Domokos & Gibbons, ; Krumbein, ; Kuenen, ; Le Bouteiller et al, ; Miller et al, ; Mills, ; Parker, ; Schumm & Stevens, ). The importance of abrasion in generating sand was confirmed by recent studies combining both field and laboratory investigations (e.g., Attal et al, ; Attal & Lavé, , ; Lewin & Brewer, ; Sklar & Dietrich, ).…”
Section: Introductionmentioning
confidence: 99%